A fracture behaviour evaluation of Glass/Elium150 thermoplastic laminate with the DCB test: Influence of loading rate and temperature. (1st January 2021) - Cadieu, L.; Kopp, J.B; Jumel, J.; Bega, J.; Froustey, C.
Abstract: The influence of loading rate and temperature on the delamination resistance of a Glass/Elium 150 laminate is studied. Double cantilever beam (DCB) tests are performed under various opening rate conditions ranging from 8.3 × 10 - 7 m . s - 1 to 0.5 m . s - 1 under isothermal condition so as at fixed opening rate condition but different temperatures ranging from - 10  °C to 60  °C. The influence of loading rate and temperature is highlighted through the evolution of the specimen stiffness, peak load, and critical strain energy release rate. Subsequently, the fracture surface is observed with scanning electron microscope (SEM) to observe the damage mechanisms for each regime. More ductile matrix failure is observed at 60 ° C which may be responsible of the specimen toughening.